The Effects of Research Activities on Biomedical Students' Mental Health: A National Cross-Sectional Study - Li, Yue; Jin, Shengyang; Li, Ya; Guo, Fei; Luo, Ting; Pan, Bo; Lei, Mingxing; Liu, Yaosheng (Frontiers in Psychiatry, 2022)
Mental health disorders are prevalent among biomedical students, and scientific research is one of their main activities, yet little is known about the relationship between research activities and mental health among these students. The aim of this cross-sectional study was to assess the associations between research activities and mental health and to identify potential risk factors for anxiety and depression among biomedical students in China. This study enrolled 1,079 participants between November 2020 and December 2020 from 29 Chinese provinces and collected participants’ basic characteristics, work situations, scientific achievements, and potential stress sources via an online questionnaire. Anxiety and depression were evaluated by two widely used scales, the Generalized Anxiety Disorder-7 (GAD-7) and the Patient Health Questionnaire–9 (PHQ-9), respectively. The study also assessed the associations between scientific research duration and mental health. Univariate and multivariate analyses were performed to identify predictors of anxiety and depression. Among the participants, 39.02% scored as having moderate to severe anxiety, and 37.54% scored as having moderate to severe depression. When the Youden index reached its maximum, the optimal cut-off was 7.17 hours for the GAD-7 and 6.83 hours for the PHQ-9. After adjustment for confounders, a longer research work duration was significantly associated with higher anxiety (odds ratio (OR) = 1.32, 95% confidence interval (CI): 1.21–1.44, P < 0.01) and depression (OR = 1.27, 95% CI: 1.17–1.39, P < 0.01). Of all the participants working for 7 hours a day, 37.04% had already published at least one paper, and 25.93% had at least one Science Citation Index (SCI) paper. Anxiety and depression are common among biomedical students. The research work duration of 7 hours a day is the best cut-off for mental health, and it is associated with acceptable scientific research achievements. No more than 7 hours a day on research is recommended for biomedical students to maintain a balance between mental health and scientific research achievements.